Traumatic Dislocations of the Sternoclavicular Joint, Methods of their Conservative and Surgical Treatment (Literature Review) - Sorokivskyi, I.R.; Kulyk , Yu.A. (TERRA ORTHOPAEDICA, 2024)
Summary. Treatment of traumatic dislocations of the sternoclavicular joint is not well defined, the results are contradictory, with a high percentage of recurrences and complications, and no differentiated approach to the choice of surgical treatment is developed, which indicates the relevance of this problem. This review describes the known methods of conservative and surgical treatment of this injury, and their effectiveness is evaluated. Objective: based on the analysis of literature on dislocation of the sternoclavicular joint, to evaluate the effectiveness of conservative and surgical treatment. Materials and Methods. The review is based on the data obtained by searching the Medline, PubMed, and EMBASE databases for the period 1951-2024. Results. We analyzed 87 sources of literature related to the treatment of traumatic dislocations of the sternoclavicular joint, of which 35 sources were identified as having quantitative characteristics and meeting the purpose of the analysis (anatomy and biomechanics – 7, conservative treatment – 7, surgical treatment – 22). Conclusions. Dislocations of the sternoclavicular joint account for 1% of the total number of dislocations and 3% of the upper extremity dislocations. The problem is the complexity of the anatomical area, low treatment efficiency, and a high rate of recurrence and complications. The main method of conservative treatment is closed reduction of the dislocation using the two techniques described below: abduction traction and the principle of a lever (caudal traction) with subsequent immobilization of the limb. Today, the choice of the optimal method of surgical treatment remains a controversial issue. There are a large number of methods of surgical fixation of the sternoclavicular joint, which may indicate the imperfection of each of them.